An Annotated List of the Lichens and Lichenicolous Fungi of the Teteriv River Basin (Ukraine) - Kapets, Nadiia (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
First data on lichens of the Teteriv River Basin appeared in the second part of 19th century. First records of lichenicolous fungi in this area were published at the end of the 20th century. An annotated list of lichens and lichenophilous fungi is based on literature data and materials of own researche of lichenobiota of the upper and middle course of the Teteriv river basin. Llist of lichens and lichenicolous fungi of the area includes 300 species. The distribution of 117 species (80 lichens, 37 lichenicolous fungi) are for the first time recorded for area studied. Five species (Cercidospora macrospora, Lichenostigma epipolina, Lichenothelia tenuissima, Polysporina subfuscescens і Taeniolella beschiana) are new to Ukraine, 7 species (Anisomeridium polypori, Coenogonium pineti, Lichenoconium usneae, Monodictys epilepraria, Rinodina efflorescens, Sphaerellothecium propinquellum, Taeniolella punctata) are new for the Ukrainian Plains, while 11 species (Cornutispora lichenicola, Erythricium aurantiacum, Heterocephalacria physciacearum, Intralichen christiansenii, Laetisaria lichenicola, Lichenothelia convexa, Marchandiomyces corallinus, Psoroglaena dictyospora, Pyrenochaeta xanthoriae, Sarcogyne lapponica, Scoliciosporum gallurae, Stigmidium xanthoparmeliarum) are new for the Polissia subprovince of mixed coniferous and broad-leaved forests, and one species is new for the territory of the Ukrainian forest-steppe subprovince. In addition, new information on the distribution of a number of rare to Ukraine lichen and lichenicolous fungal species (Absconditella lignicola, Cornutispora lichenicola, Clypeococcum hypocenomycis, Lichenochora obscuroides, Lichenodiplis lecanorae, Marchandiomyces corallinus, Psoroglaena dictyospora, Sclerococcum sphaerale, Strangospora deplanata, Thelocarpon epibolum ect.) is obtained.